Analisis Pengaruh Karakteristik Produk terhadap Niat Beli Ulang Pelanggan menggunakan Metode Regresi Logistik Biner - Faisal, Faisal; Sari, Irma Ratna; Saraswati, Iska; Heikal, Jerry (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
The internet and television have become an inseparable part of the daily life of modern society. The function of the internet covers various aspects, from communication, entertainment, education, to work. On the other hand, television remains a medium of entertainment and information for many people. This study aims to identify dependent variables and determine the accuracy of the model used by data processing using the SPSS program to find out whether customers will make a repeat purchase or not. Based on the above reasons, the analysis will be conducted to assess the influence of product characteristics on the customer's desire to repurchase the add-on or upgrade the product currently in use, in an internet and TV service company and to identify and analyze the product characteristics that most significantly affect the customer's decision to purchase the same product again in the future. The method used is binary logistic regression. The results of the study showed a significant influence between the independent variable (X) internet speed used, the type of product used, and the type of network used on the dependent variable (Y) of the decision to rebuy (add on). For the results of the binary logistic regression classification table, it is known that the results of prediction and observation are 325 customers who do not Rebuy (add on), while those who are predicted and observed do Rebuy (add on) as many as 293 customers. The remaining 214 and 168 customers produced differences between prediction and observation, so that the percentage accuracy of the regression model in this study was obtained of 61.8%. Based on the results of binary regression analysis, we found that internet speed is a very influential factor for customers in purchasing additional products. Creating variations of additional products for internet speed upgrades is crucial and should be better considered by the product team. The right variations of speed upgrades are a solution to increasing the sales of additional products.